2020
DOI: 10.3389/fpsyg.2020.566571
|View full text |Cite
|
Sign up to set email alerts
|

How to Solve the Social Norm Conflict Dilemma of Green Consumption: The Moderating Effect of Self-Affirmation

Abstract: Social norms are important social factors that affect individual behavioral change. Using social norms to promote green consumption is receiving increasing attention. However, due to the different formation processes and mechanisms of the behavioral influence of the different types of social norms, using social norms to promote green consumption often has social norm conflict situations (injunctive norms + negative descriptive norms). Thus, it is difficult to attain the maximum utility of social norms. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Another study by [130] found that dwellers' behavior is directly affected by social norms. According to [131], the result of a consumer's product intake is predetermined by social norms. When people have a negative perception of a product, their intake of that product drops dramatically [132].…”
Section: Social Norms and Willingness To Adopt Solar Pvmentioning
confidence: 99%
“…Another study by [130] found that dwellers' behavior is directly affected by social norms. According to [131], the result of a consumer's product intake is predetermined by social norms. When people have a negative perception of a product, their intake of that product drops dramatically [132].…”
Section: Social Norms and Willingness To Adopt Solar Pvmentioning
confidence: 99%
“…Personal norms can be activated when buyers become aware of their environmental responsibilities or realize adverse consequences of their behavior ( Schwartz and Howard, 1981 ; Zhang et al, 2013 ; Ge et al, 2020 ). Hafner et al (2019) concluded that normative information is highly persuasive in driving an individual’s pro-environmental behavior.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Given mounting environmental challenges, people have increasingly become more mindful of environmental concerns ( Liu et al, 2016 ; Wang Y. et al, 2019 ) and the importance of prioritizing sustainable development ( Hosta and Zabkar, 2021 ). Green consumption has become an important issue for governments, businesses, and consumers ( Ge et al, 2020 ), as about 40% of environmental deterioration can be traced directly from residential non-green consumption ( Moon et al, 2019 ). However, many still do not practice green purchasing behaviors (GPBs), especially among apathetic consumers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo (2020) examined the impact of social exclusion (i.e., being rejected, isolated, excluded, or ignored by other individuals or groups in society) on consumers' intention to consume green [10]. Ge (2020) explains the internal influence mechanism between social norm conflict and green consumption [11]. Amatulli (2019) indicates that under the influence of expected shame, negatively framed messages are more effective than positively framed ones in prompting consumers to engage in pro-environmental behaviors [12].…”
Section: Introductionmentioning
confidence: 99%